Planning calculations in cluster systems - Русанова, О. В.; Шевело, А. П. (Problems of Informatization and Control, 2008)
Dedicated to the study of various heuristic scheduled scheduling algorithms for cluster systems with a view to selecting the most effective ones. The known and the authors of the proposed approaches queuing calculations, as well as their assignment to the computers of cluster systems. A software model, with which performed a comparison of different scheduling algorithms. It is shown that the proposed algorithms have higher efficiency compared to known approaches. The validity of the results is confirmed by the algorithm on a real cluster system